From Trauma to Self-Acceptance: A Phenomenological Study of the Spiritual Experiences of Landslide Survivors - Cintami Farmawati; Anizar Rahayu; Lily Mayawati (Utan Kayu Publishing, 2026)
Landslides cause multidimensional impacts, not only psychological but also social and spiritual. This study highlights the importance of understanding survivors’ journeys toward self-acceptance, considering the limited research that emphasizes the role of spirituality in trauma recovery within the religious-cultural context of Indonesia. The study proposes to understand and describe the spiritual experiences of landslide survivors as they journey from trauma to self-acceptance. Using a phenomenological approach, data were collected through semi-structured in-depth interviews with survivors who experienced significant trauma. Thematic analysis was employed to capture psychological, social, and spiritual dynamics in participants lived experiences. The findings reveal that the survivors’ journey is transformative, characterized by phases of emotional turmoil, social disconnection, and eventually the search for new meaning through religious practices and spiritual coping. Spirituality emerged as the primary source of strength in fostering resilience and transforming suffering into post-traumatic growth. This study contributes theoretically by enriching disaster psychology literature with a focus on spirituality and meaning-making, methodologically by applying an in-depth phenomenological approach, and practically by providing a basis for developing locally grounded, spiritually oriented psychosocial interventions to support disaster survivors’ recovery.